1992
DOI: 10.1073/pnas.89.24.12185
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion toxins targeted against the sarcoplasmic reticulum Ca(2+)-release channel of skeletal and cardiac muscle.

Abstract: We report the purification of two peptides, called "imperatoxin inhibitor" and "imperatoxin activator," from the venom of the scorpion Pandinus imperator targeted against ryanodine receptor Ca2+-release channels. Imperatoxin inhibitor has a Mr of 10,500, inhibits [3Hjryanodine binding to skeletal and cardiac sarcoplasmic reticulum with an EDso of 10 nM, and blocks openings of skeletal and cardiac Ca2+-release channels incorporated into planar bilayers. In whole-cell recordings of cardiac myocytes, imperatoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 17 publications
2
104
0
4
Order By: Relevance
“…2 by fusion of rabbit junctional SR to a planar bilayer. The identification of this large unit conductance channel as the ryanodine receptor has been documented extensively [9,17,21]. In this case, the control channel activity at 0 mV was elicited by Ca" which is present in the myoplasmic-equivalent cis solution as a contaminant and is typically 1 to 3 PM free Ca".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 by fusion of rabbit junctional SR to a planar bilayer. The identification of this large unit conductance channel as the ryanodine receptor has been documented extensively [9,17,21]. In this case, the control channel activity at 0 mV was elicited by Ca" which is present in the myoplasmic-equivalent cis solution as a contaminant and is typically 1 to 3 PM free Ca".…”
Section: Resultsmentioning
confidence: 99%
“…A separate class of intracellular Ca" channels, namely ryanodine receptors, has been described in muscle and brain cells where they are believed to mediate the ubiquitous Ca"-mobilizing mechanism known as Ca"-induced Ca7+ release [7]. In skeletal and cardiac muscle, ryanodine receptors are abundant in the junctional sarcoplasmic reticulum [8] and release Ca" during excitation-contraction coupling in response to cell membrane depolarization [9]. Ryanodine receptors are activated by Ca'+ at physiological concentrations, and are modulated by a variety of ligands that affect Ca"-induced Ca7+ release such as Mg'+, adenine nucleotides and caffeine Lee [15] showed that cADPR like caffeine.…”
Section: Introduction a Well-knownmentioning
confidence: 99%
“…Imperatoxin A (IpTx a ), a 33-amino acid peptide isolated from the scorpion Pandinus imperator, was shown to be a high affinity agonist of RyR1 channels (20,21). Nanomolar IpTx a increased high affinity [ 3 H]ryanodine-binding and induced rapid Ca 2ϩ release from SR vesicles.…”
mentioning
confidence: 99%
“…Cardiac damage might be enhanced by the depressive effect of cytokines upon myocardial cells. Hyperglycemia may also contribute to myocardial injury [10]. Valdivia et al [11] reported a series of 32 children with scorpion bites who developed cardiac complications.…”
Section: Discussionmentioning
confidence: 99%